Gas Gangrene in Orthopaedic Patients - Zhimin Ying; Min Zhang; Shigui Yan; Zhong Zhu (Case Reports in Orthopedics)
Clostridial myonecrosis is most often seen in settings of trauma, surgery, malignancy, and other underlying immunocompromised conditions. Since 1953 cases of gas gangrene have been reported in orthopaedic patients including open fractures, closed fractures, and orthopaedic surgeries. We present a case of 55-year-old obese woman who developed rapidly progressive gas gangrene in her right leg accompanied by tibial plateau fracture without skin lacerations. She was diagnosed with clostridial myonecrosis and above-the-knee amputation was carried out. This patient made full recovery within three weeks of the initial episode. We identified a total of 50 cases of gas gangrene in orthopaedic patients. Several factors, if available, were analyzed for each case: age, cause of injury, fracture location, pathogen, and outcome. Based on our case report and the literature review, emergency clinicians should be aware of this severe and potentially fatal infectious disease and should not delay treatment or prompt orthopedic surgery consultation.